Optimization of Biology Learning on Excretory System Material through Contextual Teaching and Learning Approach - Tazkiyatun Nafsi Trisahid; Duangsmorn Kijkosol; Christine Corrales (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to evaluate the effectiveness of the Contextual Teaching and Learning (CTL) approach in teaching biology, particularly on the excretory system topic, by comparing it with conventional teaching methods to improve students' understanding and engagement. Methodology: This study employed a quasi-experimental method using a non-equivalent control group design. Data collection tools included pretest and posttest multiple-choice questions validated for reliability. Observations were guided by structured observation sheets. Statistical analysis utilized Kolmogorov-Smirnov, Levene’s Test, and t-tests. Data processing used SPSS software. Sampling employed purposive sampling, targeting high school biology students. Main Findings: The study found that the Contextual Teaching and Learning (CTL) approach significantly improved students’ understanding of the excretory system compared to conventional methods. The experimental group showed higher posttest scores and N-Gain values. Observations revealed better student engagement, collaboration, and contextual task-solving in the CTL group. Statistical tests confirmed the effectiveness of CTL in enhancing conceptual understanding and active learning. Novelty/Originality of this study: This study introduces the application of the Contextual Teaching and Learning (CTL) approach specifically to the excretory system topic in biology, providing empirical evidence of its effectiveness in improving understanding and engagement. It contributes new insights into the integration of contextual learning strategies in biology education, highlighting their potential to bridge theoretical knowledge with real-world applications.